2023
DOI: 10.4274/tjo.galenos.2022.70375
|View full text |Cite
|
Sign up to set email alerts
|

An Association Between the Intestinal Permeability Biomarker Zonulin and the Development of Diabetic Retinopathy in Type 2 Diabetes Mellitus

Abstract: Objectives: Increased intestinal permeability (IP) and gut microbiota dysbiosis have been implicated in low-grade chronic inflammation, which is an important factor in the pathogenesis of diabetic retinopathy (DR). This study aims to demonstrate the relationship between the IP biomarker zonulin and DR in patients with type 2 diabetes mellitus (T2DM). Materials and Methods: This study was conducted with a total of 89 T2DM patients, including 33 non-DR, 28 with nonprolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Faecal microbiota transplantation (FMT) consists of the transfer of fresh or frozen faecal material from healthy donors to a patient's intestine to restore eubiosis [235]. Although delivery through colonoscopy remains the preferred route, its intrinsic invasiveness and the risks associated with the procedure have recently led to the consideration of enema, nasogastric delivery, or oral pills as alternative transplantation techniques [236,237].…”
Section: Faecal Microbiota Transplantationmentioning
confidence: 99%
“…Faecal microbiota transplantation (FMT) consists of the transfer of fresh or frozen faecal material from healthy donors to a patient's intestine to restore eubiosis [235]. Although delivery through colonoscopy remains the preferred route, its intrinsic invasiveness and the risks associated with the procedure have recently led to the consideration of enema, nasogastric delivery, or oral pills as alternative transplantation techniques [236,237].…”
Section: Faecal Microbiota Transplantationmentioning
confidence: 99%
“…Increased gut permeability promotes low-grade systemic inflammation, which is a root cause for metabolic disorders and various chronic diseases, including type 2 diabetes [8]. These findings are supported by recent studies that found markers such as zonulin and short-chain-fatty-acid-producing bacteria in the gut to have a correlation with diabetes and its complications [8,11]. Thus, investigating the relationship between intestinal bacteria alteration and a compromised gut barrier on the development of diabetes, and the potential factors causing said changes, is imperative to attenuate the progression of prediabetes to diabetes.…”
Section: Introductionmentioning
confidence: 74%